(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This Article will deal with the role of Competition law in consumer welfare. Competition law concentrates in maintaining the process of competition between enterprises and tries to remedy behavioral or structural problems in order to re-establish effective competition in the market. The consequence of this is higher economic efficiency, greater innovation and enhancement of consumer welfare. It explains whether consumer protection is the ultimate goal of competition law or the enforcement of competition law leads to the protection of consumer interest, as a consequence